Allyl Isothiocyanate (AITC) Triggered Toxicity and FsYvc1 (a STRPC Family Member) Responded Sense in Fusarium solani - Li, Yingbin; Liu, Yixiang; Zhang, Zhiping; Cao, Yongsong; Li, Jianqiang; Luo, Laixin (Frontiers in Microbiology, 2020)
Allyl isothiocyanate (AITC) is a natural product used as a food additive. Due to its strong volatility and broad biological activity, AITC is considered as a bio-fumigant to control soil-borne fungal diseases in agriculture, creating an urgent need for evaluation of the antifungal activity of AITC. Here we study the effect of AITC on Fusarium solani growth and explore the molecular mechanisms. The results indicated that AITC causes rapid inhibition of F. solani after 5 min, hyphal deformity, and electrolyte leakage. A yeast-like vacuolar transient receptor potential channel regulator (FsYvc1, a STRPC family member) was identified in F. solani that seems to play a role in this fungi AITC sensitivity. Genetic evidence suggests the gene FsYvc1 is involved in F. solani growth, development, and pathogenicity. Loss of FsYvc1 resulted in hypersensitivity of F. solani to AITC and induced reactive oxygen species (ROS) accumulation ~ 1.3 to 1.45- folds that of the wild type (WT), and no difference responses to CaCl2, NaCl, KCl, SDS, and Congo red when compared with WT. In addition, ∆FsYvc1-17 showed significantly reduced (~ 1-fold) glutathione-S-transferase (GST) expression compared with the WT without AITC induction. Upon exposure to 4.8 μg/mL AITC for 3 h, the relative expression levels were ~ 12–30 fold higher in both the WT and ∆FsYvc1-17. Nevertheless, no difference in GST expression level was observed between the WT and ∆FsYvc1-17. The current study provides novel insights into the toxicity mechanisms of AITC. Considering our results that show the key role of FsYvc1, we propose that it could act as a new molecular target for future fungicide development.